Hydrogen electrochemical production. - Coutanceau, Christophe (Hydrogen and fuel cells primers., 2017)
Hydrogen Electrochemical Production presents different avenues of hydrogen production for energy applications, including current developments and future perspectives, using an interdisciplinary approach. Part of the Hydrogen Energy and Fuel Cell Primers series, the volume synthesizes information from many sources, making it a useful reference for industry professionals, researchers and graduate students. The book examines various methods, explaining their advantages and limitations. The water electrolysis reaction and systems are explored from different points of view, including an assessment of state-of-the-art technologies. Alternatives to water for feeding the electrolysis cell anode and for electrochemical hydrogen production (such as alcohol or other compounds from biomass) are discussed.